Disturbing the Balance – Woody Allen Reads Dostoyevsky - Bobrowski, Michał (Slavia Centralis, 2020)
This paper discusses the polemic, intertextual correspondence which occurs between Woody Allen’s drama Crimes and Misdemeanors and Fyodor Dostoyevsky’s novel The Brothers Karamazov. Through a comparative analysis, the author reveals structural analogies between both works, but also fundamental ideological differences. Dostoyevky’s approach to the subject of the moral consequences of rejection of religious faith was that of a follower of the Orthodox faith. For Allen, a similar topic became the pretext for deliberations on man’s existential solitude.
Keywords: Intertextual polemic; Orthodox faith; atheism; religious ethics; secular ethics